EKSISTENSI TRADISI BERSIH DESA BALETURI PRAMBON NGANJUK - Adelia Fikriyah Ramadhani; Muzaiyana (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2022)
Abstract: The Bersih Desa tradition is a traditional activity that is carried out once a year with the aim of praying for the safety of the village and being grateful for the blessings that have been given by God. The research entitled